Effects of Pb Intercalation on the Structural and Electronic Properties of Epitaxial Graphene on SiC. Issue 29 (13th June 2016) - Yurtsever, Ayhan; Onoda, Jo; Iimori, Takushi; Niki, Kohei; Miyamachi, Toshio; Abe, Masayuki; Mizuno, Seigi; Tanaka, Satoru; Komori, Fumio; Sugimoto, Yoshiaki
Abstract : The effects of Pb intercalation on the structural and electronic properties of epitaxial single‐layer graphene grown on SiC(0001) substrate are investigated using scanning tunneling microscopy (STM), noncontact atomic force microscopy, Kelvin probe force microscopy (KPFM), X‐ray photoelectron spectroscopy, and angle‐resolved photoemission spectroscopy (ARPES) methods. The STM results show the formation of an ordered moiré superstructure pattern induced by Pb atom intercalation underneath the graphene layer. ARPES measurements reveal the presence of two additional linearly dispersing π‐bands, providing evidence for the decoupling of the buffer layer from the underlying SiC substrate. Upon Pb intercalation, the Si 2p core level spectra show a signature for the existence of PbSi chemical bonds at the interface region, as manifested in a shift of 1.2 eV of the bulk SiC component toward lower binding energies. The Pb intercalation gives rise to hole‐doping of graphene and results in a shift of the Dirac point energy by about 0.1 eV above the Fermi level, as revealed by the ARPES measurements. The KPFM experiments have shown that decoupling of the graphene layer by Pb intercalation is accompanied by a work function increase. The observed increase in the work function is attributed to the suppression of the electron transfer from the SiC substrate to the graphene layer. The Pb intercalated structure is found to be stable in ambient conditions and at high temperatures up to 1250 °C. These results demonstrate that the construction of a graphene‐capped Pb/SiC system offers a possibility of tuning the graphene electronic properties and exploring intriguing physical properties such as superconductivity and spintronics. Abstract : The effects of Pb intercalation on the structural and electronic properties of epitaxial single‐layer graphene (SLG) grown on SiC are investigated. The Pb intercalation of the graphene layer reduces the intrinsic electron doping, and turns the initial n‐type SLG on SiC into a p‐type bilayer graphene. The Kelvin probe force microscopy measurements independently confirm the change of carrier type from electrons to holes.